IoT Devices are Being Weaponized for DDoS Attacks - Rawat, Sapna; Nafis, Md Tabrez (International Journal of Computer Sciences and Engineering, 2019)
The Internet of Things revolutions have made our live stress-free and better by giving us economical services. It always keeps us connected to the embedded system and provides value added services to humans as per their requirements. As per the research, 5 billion devices are already connected with the internet and these numbers will increase to 20 billion in few years. As we know that every cloud has a silver lining, same goes for Internet of Things. IoT devices are becoming a primary object for hacker, it is continuously alluring the attacker or intruder who tries to harness and exploit the devices. Top security concerns of IoT devices are Sensitive information disclosure, Denial of service attack, Tampering of Data and privilege escalation. Internet of Things use cloud servers to exchange information from one device to another device. But if an attacker successfully exploits the vulnerability, it could easily access, read or modify the data while performing the men in middle attack. Moreover malicious user can use this data that can cause potential damage to the targeted organization and can use it for their personal financial gain. This article provides the guidance for best practices to mitigate the DDOS attack and examine their interrelationships.